PENGARUH PEMBELAJARAN ORGANISASI, ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN - Adi Sismanto; Ade Tiara Yulinda ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
The study was conducted with the formulation of the problem in the study are: How the influence of organizational learning, market orientation and product innovation on marketing performance at BRI Bank Bengkulu Branch Based on the results of research and analysis of the effect of variables on Marketing Performance (Y) at Bank Rakyat Indonesia Bengkulu Branch can be drawn conclusions as follows: From the multiple linear regression equation can be known: Y = 0.271 + 0.332 X1 + 0.458 X2 + 0.176 X3. And that Organizational Learning (X1), Market Orientation (X2), and Product Innovation (X3) have a positive effect on Marketing Performance (Y) at the Bank Rakyat Indonesia Bengkulu Branch. Between Organizational Learning (X1), Market Orientation (X2), and Product Innovation (X3) in improving Marketing Performance have a close and positive relationship. This is evidenced from the correlation analysis R = 0.829 (82.9%) and almost close to 1. And the coefficient of determination of R2 = 0.687 or about 68.7% while 31.3% is the contribution of other variables not examined. Of all the most dominant variables is the variable that most influences on Marketing Performance (Y), at the Bank Rakyat Indonesia Bengkulu Branch, the Organizational Learning variable (X1) partially influences by 0.007 out of 30 respondents turned out to have a very significant effect because the Leaders and Unit leaders want a change in the work system and in accordance with the wishes of respondents in choosing the leadership and unit leaders they want so as to improve Marketing Performance (Y), at the Bank Rakyat Indonesia Bengkulu Branch. Keywords: Organizational Learning, Market Orientation, Product Innovation, Marketing Performance